Experimental photovoltaic-thermal Power Plants based on TESPI panel. (August 2016) - Rosa-Clot, M.; Rosa-Clot, P.; Tina, G.M.; Ventura, C.
Highlights: Experimental results of 2 pilot PV-T plants, based on TESPI panels, are presented. TESPI panels can be installed on top of existing conventional PV modules. Prototypes are made of 2 twin systems (PV and PV-T), installed in 2 Italian sites. In this paper the analysis of the PV-T systems is made at a PV string level. The performance analysis is done basing on a PV and thermal efficiency combination. Abstract: Solar energy can be used to produce thermal energy, by means of thermal solar panels and electrical energy, using photovoltaic (PV) modules. In urban and suburban areas, because of a limited number of surfaces apt for installation of solar systems, the full development of both technologies can be limited. The integration of solar, thermal, and PV modules into a single unit, the so-called photovoltaic thermal (PV-T) module, could be a possible solution to generate electrical energy and heat simultaneously on the same surface. Many technical solutions are currently available; however, in this study, the analysis is limited to liquid-cooled nonconcentrating PV-T collectors where c-Si cells are used. In particular, the experimental results of two pilot plants, based on patented panels, named TESPI – thermal electric solar panel integration, are presented. The main advantage of these modules is that they represent a retrofit of existing PV plants. In fact, they can be installed on top of conventional PV modules as they are based on the infrared filtering effect of water on solar radiation. A standard test for hybrid PV-T systems for developing new solutions and measuring their performance was designed. In order to improve the design of modules and check their behavior in typical domestic hot water systems, two different PV-T solutions, but with identical PV modules, were analyzed without the heat transfer system. The prototypes are made of two systems (PV and PV-T) installed on two Italian sites, Enna (Sicily) and Pisa (Tuscany), characterized by typical Mediterranean climate. In this study, PV-T systems were analyzed at a PV string level. Different operating conditions were tested and electrical and thermal critical operating conditions were detected.